Differentiation of live and dead Mycobacterium tuberculosis complex in meat samples using PMA qPCR. (December 2019) - Dorn-In, Samart; Gareis, Manfred; Schwaiger, Karin
Abstract: The causative agents of zoonotic bovine tuberculosis (bTB), Mycobacterium bovis and M. caprae, are members of the M. tuberculosis complex (MTC). Wildlife such as red deer infected with bTB are often without pathological findings, thus meat thereof may be classified as safe for human consumption. The culturing of MTC is time consuming and inappropriate to be applied with fresh meat and food. Therefore, a rapid method "PMA qPCR" to differentiate living and dead cells of MTC was developed in this study. By treating with 50 μM PMA™ dye, dead M. bovis BCG (≤10 4  cells/ml meat suspension) could be completely discriminated and was not detected by specific MTC PCR. The limit of detection of MTC without treatment with PMA™ dye was 10 cells/ml. All 50 venison samples obtained for field study purposes were negative for MTC. However, 40% were slightly PCR positive for non-TBC mycobacteria. By culturing using selective enrichment, one single colony of M. avium was isolated. This is the first report on the isolation of M. avium from venison. Considering the difficulties of diagnosing mycobacteria in various matrices, the developed PMA qPCR is applicable for the differentiation of dead and living cells of MTC in meat samples. Highlights: A sensitive and specific PMA qPCR was developed for discrimination of dead MTC. The limit of detection of MTC without PMA™ dye was 10 1  cells/ml meat suspension. Dead MTC ≤ 10 4  cells/ml treated with 50 μM PMA were completely discriminated. The method is applicable for sample types with high risk of MTC contamination. A non-TBC mycobacterium - M. avium - was isolated in one venison for the first time.